Integrative approaches to enhance reproductive resilience of crops for climate-proof agriculture - Agho, Collins; Avni, Adi; Bacu, Ariola; Balazadeh, Salma; Baloch, Faheem Shehzad; Bazakos, Christos; Čereković, Nataša; Chaturvedi, Palak; Chauhan, Harsh; Smet, Ive De; Dresselhaus, Thomas; Ferreira, Liliana J.; et al. (My University, 2025)
Worldwide agricultural systems are threatened by rising temperatures, extreme weather events, and shifting climate zones. Climate change-driven failure in sexual reproduction is a major cause for yield reduction in horticultural and grain crops. Consequently, understanding how climate change affects reproductive processes in crops is crucial for global food security and prosperity. The development of climate-proof crops, including maize, wheat, barley, rice, and tomato, requires new genetic material and novel management practices to ensure high productivity under less favorable conditions. Safeguarding successful plant reproduction is challenging due to the complex nature of this biological process, and therefore, a multifaceted approach is the key to success. In this review, we provide an overview of the processes underlying plant reproduction and how they are affected by different abiotic stresses related to climate change. We discuss how genetics, advanced breeding technologies, biotechnological innovations, and sustainable agronomic practices can collectively contribute to the development of resilient crop varieties. We also highlight the potential of artificial intelligence (AI) in optimizing breeding strategies, predicting climate impacts, and improving crop management practices to enhance reproductive resilience and ensure food security. Lastly, we discuss the vision of a new era in agriculture where diverse actors and stakeholders cooperate to create climate-proof crops.
Keywords: Crop resilience; Sustainable agriculture; Abiotic stress; Artificial intelligence; Breeding; Climate change; Reproduction